The Abundance of Rebon Shrimp in Labuan Sangoro Sumbawa District as supplement Material for Learning Invertebrate Zoology - Renita, Octa; Karnan, Karnan; Ilhamdi, Mohammad Liwa (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
This study was intended to analyze the abundance of rebon shrimp in the Sangoro lagoons of Sumbawa Regency. This research was conducted in Labuan Sangoro, Sumbawa Regency, West Nusa Tenggara. There were three sampling sites we choosed in this research based on the habitat characteristics, namely seagras beds, coral rubble, and mangrove area. We implemented the swept area technique to collect samples using scoop net with 60 cm length, 20 cm width, and 0,5mm mesh size. Rapia ropes were pulled along 50 m for each transect line drawn perpendicular to the shoreline. next, four 10 m transect lines were drawn parallel to the shoreline. The sampling was done by pulling the scoop net along the line transect so that a volume of the scoop net was obtained. In addition, the number of individuals was counted in each 10 m transect line. This research showed that only one species of rebon shrimp found in reseach area, namely Acetes Intermedius. Among three sampling sites, the mangrove area has a highest abundance of shrimp (12506,7 ind/L), followed by seagrass beds area (12189,0 ind/L), and coral rubble area (5102,8 ind/L). It can be concluded that mangrove and seagrass beds are habitat mosly prefered by rebon shrimp.